Zasłużony najemnik w konstantynopolitańskim więzieniu. Zagadkowa rola Haralda Hardrady w rewolcie 1042 roku = A recognised mercenary in the Constantinople prison. A mysterious role of Harald Hardrada in the revolt as of 1042 - Lubik, Maciej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Harald Hardrada (about 1015-1066), the king of Norway, earlier the commander of Scandinavian mercenaries fighting for the Prince of Rus Yaroslav the Wise as well as for the Bizantine emperors (there as akoluthos ? the commander of Varangian Guard) is a character whose history still raises doubts and leaves a lot of unanswered queries. It is due to all these inaccuracies of Scandinavian sources (mainly Heimskringla, Fagrskinny and Morkinskinny) as well as the absence of information concerning his deeds in the Rus and Bizantine?s sources (the only one who briefly mentions Harald is Kekaumenos, the author of the Advice for the Emperor).
Keywords: Harald III Srogi (król Norwegii; ca 1015-1066); Bizancjum; 11 w.